Formation of upwarped mountains by horizontal compression of lithosphere in shear layers model: A review - ORVOŠ, Peter (Contributions to Geophysics and Geodesy, 2011)
The understanding of mountain uplift, especially the intraplate ranges and plateaus, still remains insufficient despite advancement in the last decade. Upwarped mountains are one general category, where uplift virtually comes from the bottom by an unspecified mechanism. Several sandbox and finite-width wedge models showed that this upwarping is a natural consequence of horizontal compression of lithosphere. The model of shear layers, presented here, is derived from general theory of plasticity and represents a similar solution of the problem. But its ability to describe deformations in deeper lithosphere can be useful in studying development and changes of mountain roots. Comparison of these models, regarding their specific character, may help to understand overall morphology and tectonics of the mountains.